'This game is not easy to play': a narrative inquiry into a novice EFL teacher educator's research and publishing experiences. Issue 3 (27th May 2017) - (Eric) Yuan, Rui
Abstract : Drawing on the approach of narrative inquiry, this study looks into how a novice language teacher educator constructed and reconstructed his professional identities through his research and publishing practice in the higher education context in Hong Kong. The findings of the study show that the participant constantly tried to defend and develop his identity as a 'language teacher educator-researcher', which was subjected to various contextual obstacles including the institutional policy, the 'publish-or-perish' culture and the potential bias against practice-oriented research and peripheral research contexts. This study contributes to our understanding of the challenges and complexities involved in novice teacher educators' identity construction. The study also offers some practical implications for both language teacher education and higher education on how to help teacher educators construct a solid and strong researcher identity to support their professional practice and development.